Mulheres e tatuagens: valores e intenções impregnados na construção do corpo feminino - Andrade, Priscila Aparecida Martins [UNESP] (2015)
Tattoo is a body marking used for centuries, since ancient age until the contemporary, the new paradigm in which it is, it happens due to the way how is recognized and adopted in many different cultures and ages. The problematics of this study refers to this aspect, to understand the tattoo as a whole and then discuss how the tattoo happens in working-class women. Being a mark that still suffers prejudices, so stigmatized, we will analyse through the condition of being a woman and belonging to a poor class if that prejudice becomes bigger or not, if there is a difference in male and wealthiest class. Before this reality this study intends to perform an analysis of the tattoo's history, showing its appearance over the centuries, its modifications, prejudice and stigma, to understand it and understand through history why this prejudice perpetuate until today. The approach of the individuals who are part of this group and how they are seen will be discussed by various authors that boarded this theme too. The body, place where the tattoo appears to express feelings that are often dreams, achievements, wishes or simply fashion through the epidermis will also be reviewed. It will be added to this research Pierre Bourdieu's studies and employees about to references on women and the working classes. To obtain this objective it was looked through the qualitative methodology and as and like the form of data collection of the semistructured interview, analyzes what women interviewed think, passed and how they live with their tattoos. The results showed us that although women have autonomy and freedom is controlled by the choices of designs and local adopted to be made, this setting is performed sometimes by boyfriends or husbands, identically are regulated by the discretion of the trial of society, a conditioned liberty to a third ...